Pedagogical Experience of Teaching Financial Coaching - Lucy M Delgadillo Ph.D (Journal of Financial Therapy, 2016)
This study reports on the pedagogical experience of teaching a financial coaching course to personal and family finance undergraduate students at XXXX State University. The paper describes the conceptualization of the class, including theoretical frameworks, ethical considerations, practitioner’s models, learning objectives, and competencies. The assessment of the course provided data used by the instructor to refine and adjust future course content and assignments. Quantitative data was collected in pre- and post-tests assessments. The quantitative assessment shows statistically significant gains in specific coaching skills and competencies. The qualitative assessment indicates that, at the end of the course, students had better understanding of the coaching code of ethics and better communication and listening skills. The peer-to-peer coaching exercise was apparently very fear-provoking but valuable for the students. Challenges for teaching financial coaching by future instructors are discussed in the last section
Keywords: financial coaching; teaching; financial counseling